Study on the behavior of concrete-filled square double-skin steel tubular stub columns under axial loading. (February 2020) - Ding, Fa-xing; Wang, Wen-jun; Lu, De-ren; Liu, Xue-mei
Abstract: This paper presents a numerical, experimental, and theoretical study on the behavior of concrete-filled square double-skin steel tubular (CFDST) stub columns under axial compressive loading. Firstly, three-dimensional solid model of CFDST stub columns was established by ABAQUS finite element software and verified through the existing experimental results. Then a full-scale model was established to investigate the influence of various parameters on ultimate bearing capacity and internal and external compressive stress of concrete. By considering the confinement coefficient, the practical calculation formula for the bearing capacity of CFDST stub columns was proposed. Finally, the experimental research on the mechanical properties of two large hollow ratio CFDST stub columns under axial compression was carried out. And the experimental research further verified the applicability of the FE model and calculation formula of the CFDST stub column with large hollow ratio under axial compression.